2014
DOI: 10.2217/whe.14.18
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Dual-Energy Mammography: A Promising New Imaging Tool in Breast Cancer Detection

Abstract: Contrast-enhanced dual-energy mammography (CEDM) is a promising new breast imaging tool for breast cancer detection. In CEDM, an iodine-based contrast agent is intravenously administered and subsequently, dual-energy mammography is performed. This results in a set of images containing both a regular mammogram and an image that contains contrast enhancement information. Preliminary studies have indicated that CEDM is superior to conventional mammography and might even match the diagnostic performance of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…In CESM, an iodine-based contrast agent is intravenously administered, after which dual-energy mammography is performed. As a result, the radiologist can view a low-energy image (which is similar to a conventional FFDM) and a recombined image, showing areas of enhancement [7, 16]. In a previous study, it was shown that CESM is an excellent problem-solving tool for women recalled from the breast cancer screening program [5].…”
Section: Discussionmentioning
confidence: 99%
“…In CESM, an iodine-based contrast agent is intravenously administered, after which dual-energy mammography is performed. As a result, the radiologist can view a low-energy image (which is similar to a conventional FFDM) and a recombined image, showing areas of enhancement [7, 16]. In a previous study, it was shown that CESM is an excellent problem-solving tool for women recalled from the breast cancer screening program [5].…”
Section: Discussionmentioning
confidence: 99%
“…CESM is a promising new breast imaging modality that has been shown to be superior to conventional mammography in the detection of breast cancer [ 2 , 3 , 10 ]. No studies so far have compared the quality of the LE images to that of FFDM in a standardized and structured manner, using well established EUREF image quality criteria.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is contrast-enhanced spectral mammography (CESM). Recent studies continue to show that CESM is superior to conventional mammography in breast cancer detection [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods each have their own limitations in sensitivity, specificity, spatial resolution, radiation dose, availability, cost, and other barriers to widespread adoption [7][8][9]. Contrast-enhanced dual-energy mammography, which utilizes conventional mammography and iodinated contrast agents to distinguish tumors via vascularity, was recently demonstrated to exhibit detection rates comparable to MRI [10,11].…”
Section: Introductionmentioning
confidence: 99%